Revisiting the Case Study Method in Social Research: A Reflective and Argumentative Review for Novice Researchers - Pokharel, Keshab Raj; Paudel, Srijana; Marasini, Amrit (Educational Journal, 2024)
This article provides a qualitative review of case study method in social research. The core purpose of this paper is to guide novice researchers in doing case study to explore complex social phenomenon. It begins by clarifying foundational concept of case study and its purpose. It highlights the historical evolution of case study research beginning from Frederic Le Play during 18th century to three key methodologists, Robert K. Yin, Robert E. Stake, and Sharan B. Merriam. It further presents definition, purpose, and philosophical stance of case study from these key philosophers’ perspectives. Based on general qualitative research design it provides detailed exploration of philosophical underpinnings including ontology, epistemology and axiology to guides researcher on making better choice of design and interpretation of case studies. Key features that distinguish case study, like intensive focus on bounded system, holistic exploration, rich description, multiple sources of evidence, and flexibility in design types as defined by Yin and Stake are highlighted. Further, it provides the overview of data collection tools, analysis procedures, and strategical considerations to be followed. Finally, it examines this methodology critically to mention inherent challenges and limitation of case study. This paper integrates theoretical insight with methodological guidance that can serve as the foundational source for early-career researchers. It can be helpful to those researchers who wants to adopt or better understand case study method in social inquiry.